The entry of the newly-ordained bishop Pachomius to Rostov on 28 january 1215: the choice of the day for the solemn ceremony - Aleksei Laushkin (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2019)
The article is devoted to the calendar component of the solemn entries of the newly-consecrated bishops into their diocesan capitals in Rus’ until the end of the 13th century. The author shows that, in their absolute majority, ceremonies of this kind dated in sources occur on Sundays or holidays, or their eves. This makes it possible to speak of a meaningful choice of time for their holding and of life in Rus’ (at least from the beginning of the 12th century, when the earliest data appear) of a pronounced “festive strategy” in their planning. Against this background stands out the entrance to Rostov after Bishop Pachomius was ordained on January 28, 1215, it occurred on an ordinary Wednesday. Analyzing the preserved sources, the author suggests that the organizers of the ceremony were attracted by the feast of St. Ephraim Sirin that was celebrated on that day, when in Rostov they could prayerfully commemorate the eponymous bishop who once led the Rostov diocese. The author believes that the timing of the ceremony for such a day was relevant in the context of a sharp political struggle that began in Suzdal land after the death of Grand Prince Vsevolod the Big Nest in 1212 and led, among other things, to the schism of the previously united Rostov Diocese in 1214– 1215. According to the author, the possibility of such an interpretation is confi rmed by the attentive attitude of Prince Konstantin Vsevolodovich, who ruled in Rostov at that time, to the choice of days for solemn ceremonies in which he took part.